Legal Analysis Of Law Enforcement Against Children As Perpetrators Of Sexual Abuse From A Restorative Justice Perspective - Nia Agustri Lase; Fitria Ramadhani Siregar; Muhammad Arif Sahlepi (JURNAL HUKUM SEHASEN, 2026)
Law enforcement against children as perpetrators of sexual abuse often faces a dilemma between the principles of child protection and restorative justice. This study aims to analyze the legal application of restorative justice in cases involving children who commit sexual abuse in Indonesia, focusing on Law No. 11 of 2012 concerning the juvenile criminal justice system and Law No. 35 of 2014 concerning child protection. The approach used is normative legal analysis of legislation, court decisions, interviews, and literature studies. The results show that restorative justice can be an effective alternative to reduce stigmatization and support the rehabilitation of child perpetrators, but its implementation is still hampered by a lack of coordination between institutions, such as the police, prosecutors, and child protection agencies, as well as minimal victim participation in the mediation process. The restorative justice perspective offers a holistic approach that prioritizes the restoration of social relationships, the prevention of recidivism, and children's rights, but requires regulatory strengthening to ensure balance with the rights of victims.